Department Conditions and Practices Associated with Faculty Workload Satisfaction and Perceptions of Equity. (3rd September 2019) - O'Meara, KerryAnn; Lennartz, Courtney Jo; Kuvaeva, Alexandra; Jaeger, Audrey; Misra, Joya
ABSTRACT: For decades, national surveys have shown faculty report high levels of dissatisfaction with the distribution of labor in their departments, especially women and underrepresented minority faculty. Research suggests this dissatisfaction is warranted, as these groups are often engaged in more service, mentoring, and institutional housekeeping than their peers. Despite the ample work revealing workload inequities and their consequences, few studies have examined the backdrop of conditions and practices within which workload is perceived as more or less fair, especially within departments. Drawing on survey data from 30 academic departments in Maryland, North Carolina, and Massachusetts, we empirically test three propositions about the conditions under which faculty experience their department workloads as equitable. We found departments where faculty reported equitable work conditions and practices (e.g., transparency, clarity, rotations of time-intensive roles) were significantly more likely than departments where faculty did not report these conditions and practices to report satisfaction with workload distribution, and satisfaction with teaching and service activities. Department work practices and conditions had a small or insignificant effect on faculty intent to leave. Interestingly, faculty confidence in the ability to enact these practices and conditions, which we termed action readiness, was not predictive of faculty satisfaction with workload distribution or teaching and service activities. We outline implications for academic leaders seeking to make academic workloads more transparent and equitable, and for future research.